HARMONIZATION, MICROPIGMENTATION, HEALTH, BEAUTY AND WELL-BEING - Mendes Sampaio, Fernanda; Cesty Borda de Saenz, Charlotte (Health and Society, 2023)
Micropigmentation is associated with the beautification and aesthetic harmony of people. For the most part, women seek to satisfy their ego when it comes to a refinement of female beauty and a greater emphasis on their appearance in order to raise self-esteem and attract opportunities in the most varied fields of activity. In this context, there is always a harmony that is associated with micropigmentation and beauty to enhance people’s well-being.